Bronchoscopic Voriconazole Instillation in Pulmonary Aspergilloma: A Single Center Experience - Shrestha, Prajowl; Dhungana, Ashesh (Nepalese Medical Journal, 2019)
Introduction: Saprophytic growth of Aspergillus species in preexisting lung cavities commonly presents with hemoptysis. Surgical resection is the preferred treatment for hemoptysis control in pulmonary aspergilloma. In patients, who are not candidates for surgical resection bronchoscopic Voriconazole instillation, is an effective option. Materials and Methods: In this retrospective study, data of patients presenting with active hemoptysis, radiological evidence of aspergilloma and those undergoing bronchoscopic Voriconazole instillation at National Academy of Medical Sciences from January 2018 to December 2018 were retrieved. Clinical details including the severity of hemoptysis, number, size and location of aspergilloma, number of Voriconazole instillation sessions and symptom control were assessed. Follow up CT scan after four to six sessions were also evaluated to compare the size of aspergilloma. Results: A total of 11 patients presented with aspergilloma and hemoptysis. Of these, five (45.4%) patients underwent at least four sessions of bronchoscopic Voriconazole instillation. Two patients required six sessions whereas one required nine sessions for hemoptysis control. The procedure was successful in all patients; however, one had a recurrence after 3 months and required bronchial artery embolisation. In four patients there was a reduction in the size of aspergilloma on follow up CT scan. The procedure was well tolerated by all the patients, except for a mild increase in cough in the immediate post-procedure period. Conclusions: Intrabronchial Voriconazole instillation is a safe and effective option for hemoptysis control in patients with pulmonary aspergilloma. However, the optimal dose, frequency, and duration of Voriconazole instillation need to be further evaluated.